2020
DOI: 10.1042/bsr20200764
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the prognostic significance of solute carrier (SLC) family 39 genes in breast cancer

Abstract: Background: Breast cancer (BC) is the most common malignancy in females and remains a main cause of cancer-associated death worldwide. The solute carrier (SLC) groups of membrane transport proteins, which control the influx of zinc, participate in ranging of physiological processes and may provide novel therapeutic targets of cancers. However, the prognostic values of individual SLC family 39 (SLC39A) genes in patients with BC are not clarified. Materials and Methods: The mRNA expression of SLC family 39 genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 47 publications
2
23
0
Order By: Relevance
“… 34 SLCA39 has been reported to play important roles in the development of various malignant tumors, such as esophageal cancer, colorectal cancer, prostate cancer, lung cancer, and hepatocellular cancer. 35 In addition, some studies have indicated that SLCA39A8 plays an important role in the regulation of IFN‐γ expression in T cells and is closely associated with the development of hepatocellular carcinoma. 36 , 37 SOCS1 belongs to the SOCS protein family, which is highly specific in controlling the activity of some cytokines.…”
Section: Discussionmentioning
confidence: 99%
“… 34 SLCA39 has been reported to play important roles in the development of various malignant tumors, such as esophageal cancer, colorectal cancer, prostate cancer, lung cancer, and hepatocellular cancer. 35 In addition, some studies have indicated that SLCA39A8 plays an important role in the regulation of IFN‐γ expression in T cells and is closely associated with the development of hepatocellular carcinoma. 36 , 37 SOCS1 belongs to the SOCS protein family, which is highly specific in controlling the activity of some cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…The antibody recognizing phosphorylated ZIP7, the zinc-transporting form ( 113 ), is a reliable marker of aggressive cancer ( 252 ). ZIP7 is also associated with poor outcome in clinical breast cancer samples ( 253 ), consistent with a role in driving these aggressive growth pathways, yet it has also been deemed crucial for enabling the survival of breast cancer patients ( 254 ). Since elevated cellular zinc levels generally encourage cells growth and proliferation, a growing variety of cancers has been associated with upregulations of multiple ZIPs.…”
Section: Zinc Transporters and Human Diseasesmentioning
confidence: 98%
“…Some of the genes have also been associated with development of specific tumors, e.g. TAC4 [ 5 ], IGSF1 [ 17 ] and SLC39A8 (ZIP8) [ 24 ]. A prognostic role has also been reported for some of these genes, both negative ( ERRFI1 ) [ 25 ], and positive ( SLC44A3 ) [ 29 ].…”
Section: Resultsmentioning
confidence: 99%